Occupational exposure to fine particulate matter in the reinforced concrete production and its association with respiratory symptoms and lung function - Denis Vinnikov; Anel Abenova; Aizhan Raushanova; Venerando Rapisarda (BMC Public Health, 2023)
Abstract Background Reinforced concrete production is widespread, but little is known about the occupational exposure to fine particulate matter (PM) in such workplaces, including from metalworking and concrete processing. Therefore, the aim was to characterize exposure to fine PM in the typical workplaces of the whole production cycle and to quantify the risk of respiratory symptoms and lung function in a cohort of reinforced concrete parts production industry. Methods At a reinforced concrete parts producing facility in Almaty, we collected 50 personal PM2.5 samples from the main exposure sites and the measured mass concentrations using gravimetric method. Workers also completed questionnaires on a detailed working history, respiratory symptoms (chronic obstructive pulmonary disease (COPD) Assessment Tool (CAT)), followed by spirometry. The association of cumulative dose with CAT score and forced expiratory volume in one second (FEV1)/forced vital capacity (FVC) was tested with multiple regression. Results The highest PM2.5 concentrations were found in the concrete-mixing unit (median 1180 µg/m3), followed by metalworking (510 µg/m3), armature workshop (375 µg/m3) and molding site (245 µg/m3), different from the concentrations in the office (29.5 µg/m3), Kruskall-Wallis p < 0.001. Cumulative PM2.5 dose, mg/m3-year (beta 0.10 (95% confidence interval (CI) 0.05; 0.15)) was strongly associated with CAT score, whereas production with FEV1/FVC (beta -4.96 (-8.31; -1.61)), independent of smoking and chronic bronchitis and sex. Conclusions Mixing concrete and metalworks pose the greatest risk for worker’s health in the reinforced concrete production from the inhalational exposure to aerosol, adversely affecting respiratory health.